Pengaruh Kinerja Keuangan Terhadap Harga Saham Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Yusnita, Irni; Dewi, Winona Kumara; Putri, Maharani (Universitas Palangka Raya, 2025)
Banks are a very important intermediary institution to support all economic activities in society. In general, investors are interested in seeing how financial performance can find predictions of future stock prices. Therefore, the relationship between financial performance and stock prices is considered very important, especially in the banking industry. This study investigates the impact of financial performance indicators Return on Assets (ROA), Return on Equity (ROE), Earnings Per Share (EPS), and Price Earning Ratio (PER) on the stock price of banking companies listed on the Indonesia Stock Exchange in 2019- 2023. Using secondary data from published financial statements, this study employs multiple linear regression analysis to assess the relationship between the independent variables and the dependent variable, the stock price. The findings show that ROA, ROE, EPS and PER have effect on stock price, The overall model shows that these financial indicators collectively explain 62.9% of the variance in stock prices. The results of this study underscore the importance of ROA and ROE as key determinants of stock valuation in the banking sector, providing valuable insights for investors and stakeholders in making appropriate investments.